2013
DOI: 10.1111/j.1521-0391.2013.12083.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of reported peyote use 1985–2010 effects of the American Indian Religious Freedom Act of 1994

Abstract: Beyond describing peyote use rates and the effects of the AIRFA, this research adds to the body of evidence regarding the levels of under-reporting of illicit drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…After peyote use for ceremonial purposes was decriminalised in the USA in 1994, self-reported use increased among American Indians. 88 Three studies evaluated relationships between decriminalisation and drug-related criminal justice involvement in Mexico and the USA. One high-quality study found that decriminalisation positively influenced criminal justice involvement: in five US states, arrests for cannabis possession decreased among youth and adults.…”
Section: Impacts Of Decriminalisationmentioning
confidence: 99%
“…After peyote use for ceremonial purposes was decriminalised in the USA in 1994, self-reported use increased among American Indians. 88 Three studies evaluated relationships between decriminalisation and drug-related criminal justice involvement in Mexico and the USA. One high-quality study found that decriminalisation positively influenced criminal justice involvement: in five US states, arrests for cannabis possession decreased among youth and adults.…”
Section: Impacts Of Decriminalisationmentioning
confidence: 99%
“…In this context, peyote is not viewed as a drug, but rather as medicine for healing. The 1994 amendment to the American Indian Religious Freedom Act legalized the use of peyote for this purpose (Prue, 2014).…”
Section: Native American Peyote Usementioning
confidence: 99%
“…While significant changes in the peyote market supply have taken place in the last twenty years, the NAC of North America (NACNA) was already declaring a peyote supply "crisis" in 1995 (The New York Times 1995), a year when demand was estimated at between 5 and 10 million buttons (Anderson 1995). NACNA issued a statement reiterating these same concerns in 2012, concerns likely exacerbated by increases in NAC membership (Prue 2014), declaring that "the peyote that is available to the NAC is of a significantly diminished size, and at times there is no supply at all" (Arkinson 2012:2). Long-standing concern within the NAC, including planning efforts to maintain sufficient access to peyote through importation from Mexico or cultivation (Anderson 1995;Arkinson 2012;The New York Times 1995), suggest that demand has not diminished and supports the conclusion that the problem lies with overall supply.…”
Section: Peyote and The Peyote Tradementioning
confidence: 99%
“…Since then, it has grown into the largest Pan-Indian religion in the United States. Estimates on NAC membership range from 250,000 to 400,000 (Long 2000), and up to 600,000 (Prue 2014). Determining actual NAC membership levels is difficult because the NAC is not a single organization but rather a broad set of loosely related churches.…”
Section: Nac Membersmentioning
confidence: 99%
See 1 more Smart Citation